Design and analysis of planar spiral resonator bandstop filter for microwave frequency - Motakabber, S. M. A.; Suharsono, Muhammad Shaifudin (IOP Publishing, 2017)
In microwave frequency, a spiral resonator can act as either frequency reject or acceptor circuits. A planar logarithmic spiral resonator bandstop filter has been developed based on this property. This project focuses on the rejection property of the spiral resonator. The performance analysis of the exhibited filter circuit has been performed by using scattering parameters (S-parameters) technique in the ultra-wideband microwave frequency. The proposed filter is built, simulated and S-parameters analysis have been accomplished by using electromagnetic simulation software CST microwave studio. The commercial microwave substrate Taconic TLX-8 has been used to build this filter. Experimental results showed that the -10 dB rejection bandwidth of the filter is 2.32 GHz and central frequency is 5.72 GHz which is suitable for ultra-wideband applications. The proposed design has been full of good compliance with the simulated and experimental results here.